Business Strategies for Carbon Fiber-reinforced Polymer Recycling in the Aviation Industry: A Literature Review - Arshi Naim; Shad Ahmad Khan; Praveen Kumar Malik (Universitas Pasundan, 2024)
In the current scenario transport industry has been found using light weighted materials for external structures. Automobile, Aviation, Trains, all are showing great interests in using Carbon fiber-reinforced polymers (CFRPs) because it is not only light weight but resistance to erosion and several functional elements which are helpful in the transport industry. However the CFRP composites (CFRP-Cs) have disadvantage of recycling process due to its compounds, the recycling process can be only conducted in the extreme conditions and yet direct reuse of these CFRP-Cs are difficult to be processed. This study is investigates the business management strategies for making the CFRP-Cs applications effective and prolonged in the aviation industry. This research studies and review the use and state of art CFRP fiber, the process of recycling adopted their challenges, benefits, and guidelines. The existing state of art has suggested that CFRP use cannot be prevented but for sustainability of environment business strategies should create the market of CFRP recycling and generate consent for progressive use of recycled materials between industries in sliding directive for the necessary mechanical performance of the CFRP-Cs.